2015
DOI: 10.1186/s12884-015-0435-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of delays in travelling to an emergency obstetric care facility in Herat, Afghanistan: an analysis of cross-sectional survey data and spatial modelling

Abstract: BackgroundWomen’s delays in reaching emergency obstetric care (EmOC) facilities contribute to high maternal and perinatal mortality and morbidity in low-income countries, yet few studies have quantified travel times to EmOC and examined delays systematically. We defined a delay as the difference between a woman’s travel time to EmOC and the optimal travel time under the best case scenario. The objectives were to model travel times to EmOC and identify factors explaining delays. i.e., the difference between emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 25 publications
5
44
1
4
Order By: Relevance
“…This implies that many mothers were spent their time walking on foot as well as were carried by wooden stretchers to reach nearby health centers. 12 However, the findings of this study are lower than the study findings in Pakistan, 74%, 15 in Afghanistan, 65%, 21 in Egypt, 55.3%. 22 This might be the time gap of the study, road, and telecommunication infrastructure improvements, and expansion and closeness of health facilities to the community.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…This implies that many mothers were spent their time walking on foot as well as were carried by wooden stretchers to reach nearby health centers. 12 However, the findings of this study are lower than the study findings in Pakistan, 74%, 15 in Afghanistan, 65%, 21 in Egypt, 55.3%. 22 This might be the time gap of the study, road, and telecommunication infrastructure improvements, and expansion and closeness of health facilities to the community.…”
Section: Discussioncontrasting
confidence: 60%
“…This implies that women have difficulty to obtain transportation services, which may require more relatives to accompany as well as walking on foot for a long time, which in turn can be the cause of women's face obstetric complications, consequently influence timely reach to nearby health facility to receive institutional delivery service. 21 Further, the study showed that mothers with unemployed husbands were more likely to face a second delay in utilizing institutional delivery service when compared to those mothers with employed husbands. This may be explained with the husband was not involved in income-generating activities, which in turn can be directly the cause of women to have not accessing to transportation service even if transportation service is available as well as needs more relatives to accompany at times of referrals in case of emergencies.…”
Section: Discussionmentioning
confidence: 87%
“…Further research is needed to identify common infections contributing to stillbirth in this setting. Hirose et al identified that care‐seeking delays in Afghanistan were higher among women experiencing severe infections compared to other complications with more concerning symptoms, so it would be important to ensure early detection and management of both bleeding and infections by educating women and family members on the urgency of care‐seeking for symptoms. Headaches during pregnancy were also a strong risk factor of both stillbirth and intrapartum stillbirth and likely a sign of pre‐eclampsia or pregnancy‐induced hypertension, which are known risk factors for stillbirth.…”
Section: Commentmentioning
confidence: 99%
“…This will lead to a delay in decision making which results in maternal death [2,13] Husband's perception is very strong in determining that the mother should be referred to as mother's education, because of the cultural context where the husband is the mother's companion who will decide on the health conditions that occur in the family. However, maternal education is very beneficial to her in order to immediately find out the signs of abnormalities that occur so that they can seek immediate health help [14]. The decision to get the treatment for the family was decided by the husband, but the husband sometimes went to work from the morning, so the mother had to wait until the night when the husband came home to get medical help.…”
Section: Traditional Beliefs Embraced By Certain Communities Willmentioning
confidence: 99%